A review of applications of satellite earth observation data for global societal benefit and stewardship of planet earth. (May 2016) - Kansakar, Pratistha; Hossain, Faisal
Abstract: Remotely sensed data can be used to understand and devise measures to address important global issues such as climate change, disaster and disease outbreak. National Aeronautics and Space Administration (NASA) is one of the largest producer and gatekeeper of satellite earth observation (EO) data that plays a crucial role in ensuring that these resources are used for solving global societal problems. However, the extent of remote sensing application is highly disparate in different parts of the world. This paper provides a general overview of key societal applications that have been enabled globally with the use of EO data. It also summarizes the impact of various NASA-supported programs for promoting applications on the targeted beneficiary communities. The themes addressed here are land cover/land use mapping, carbon biomass assessment, food security, disaster management, water resources, ocean management and health and air quality. The paper also argues for capacity building that is crucial to building sustainable solutions when using EO data for science-based decision making.